Mastering System Center Data Protection Manager 2007 - Ganger, Devin L.; Femling, Ryan, 1975- (Wiley Pub., 2008)
Simple backups are no longer enough. To fully protect a modern IT infrastructure, you need sophisticated data protection technologies. This comprehensive guide to Microsoft's new System Center Data Protection Manager 2007 (DPM) will help you improve your server security using this robust new software. The book thoroughly explains DPM's unique abilities, and you'll find step-by-step instructions on setting up and deployment. You'll learn how to recover critical data and monitor processes for Exchange Server, SQL Server, SharePoint Server, Microsoft Virtual Server virtual machines, and Windows file servers and workstations.